1996
DOI: 10.1007/bf00049330
|View full text |Cite
|
Sign up to set email alerts
|

A promoter identified in the 3? end of the Ac transposon can be activated by cis-acting elements in transgenic Arabidopsis lines

Abstract: In experiments directed to develop a promoter trap strategy in Arabidopsis, using a Ds chimaeric element containing a promoterless beta-glucuronidase (GUS) gene, we identified a promoter in the 3' end region of the Ac transposable element. The promoter initiates most of the transcripts at coordinate 4250 in the Ac sequence and is oriented towards the internal part of the element. When fused to a promoterless GUS gene, the promoter allows transient expression in Arabidopsis leaves. After stable integration into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…One likely explanation is that both the T-DNA and the Ds element harbor some promoter-like activity that enables transcription of CCDA. The Ds element is known to carry a promoter-like sequence at its 3Ј-end that can be activated upon integration (51). Indeed, we could detect a hybrid RNA in the ccda-2 line using a Ds element-specific primer and a CCDAspecific primer (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…One likely explanation is that both the T-DNA and the Ds element harbor some promoter-like activity that enables transcription of CCDA. The Ds element is known to carry a promoter-like sequence at its 3Ј-end that can be activated upon integration (51). Indeed, we could detect a hybrid RNA in the ccda-2 line using a Ds element-specific primer and a CCDAspecific primer (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Although the gene trap system was designed to recover insertions within transcription units, in some lines insertions were found outside of transcribed regions (;50% of lines reported here) or within a transcribed region of an annotated gene but in the wrong orientation (;25% of lines reported here). Theoretically, no GUS staining should be observed in such a scenario; however, it has been postulated that the GUS gene in the Trapper gene trap lines may contain a minimal promoter and can also act as an enhancer trap (Cocherel et al, 1996). Gene trap insertions within transcribed regions of annotated genes yet in the opposite direction may be tagging the antisense transcripts, since many Arabidopsis genes are also transcribed in the reverse direction (Yamada et al, 2003;Jen et al, 2005).…”
Section: Gene Trap Screeningmentioning
confidence: 99%
“…Two of our Arabidopsis secretion trap lines have a single insertion outside annotated genes (GT5211 and GT6249). We considered the possibility that transcription could initiate within the gene trap element (Cocherel et al, 1996) and come under the control of a tunicamycininduced enhancer, but tests indicated that these insertions are not transcriptionally induced by tunicamycin (Table III). Furthermore, GUS expression patterns were specific to individual cell types, suggesting that they do not reflect rogue transcription.…”
Section: Insertions Outside Annotated Genesmentioning
confidence: 99%